Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To solve the equation [tex]\(\frac{3}{5}(x-4)+\frac{6}{7}=\frac{1}{7}(x+2)\)[/tex], we can follow these steps:
1. Distribute and simplify both sides:
[tex]\[ \frac{3}{5}(x - 4) + \frac{6}{7} = \frac{1}{7}(x + 2) \][/tex]
Distribute [tex]\(\frac{3}{5}\)[/tex] on the left side:
[tex]\[ \frac{3}{5}x - \frac{3}{5} \cdot 4 + \frac{6}{7} = \frac{3}{5}x - \frac{12}{5} + \frac{6}{7} \][/tex]
Distribute [tex]\(\frac{1}{7}\)[/tex] on the right side:
[tex]\[ \frac{1}{7}x + \frac{1}{7} \cdot 2 = \frac{1}{7}x + \frac{2}{7} \][/tex]
Now we have:
[tex]\[ \frac{3}{5}x - \frac{12}{5} + \frac{6}{7} = \frac{1}{7}x + \frac{2}{7} \][/tex]
2. Combine like terms:
To simplify, it is beneficial to get rid of the fractions by finding a common denominator. The common denominator for 5 and 7 is 35.
Multiply through by 35:
[tex]\[ 35 \left( \frac{3}{5}x - \frac{12}{5} + \frac{6}{7} \right) = 35 \left( \frac{1}{7}x + \frac{2}{7} \right) \][/tex]
Simplifying each term:
[tex]\[ 35 \cdot \frac{3}{5}x = 21x, \quad 35 \cdot \frac{12}{5} = 84, \quad 35 \cdot \frac{6}{7} = 30 \][/tex]
[tex]\[ 35 \cdot \frac{1}{7}x = 5x, \quad 35 \cdot \frac{2}{7} = 10 \][/tex]
So, the equation becomes:
[tex]\[ 21x - 84 + 30 = 5x + 10 \][/tex]
3. Combine like terms and isolate [tex]\(x\)[/tex]:
Simplify the equation:
[tex]\[ 21x - 54 = 5x + 10 \][/tex]
Subtract [tex]\(5x\)[/tex] from both sides:
[tex]\[ 16x - 54 = 10 \][/tex]
Add 54 to both sides:
[tex]\[ 16x = 64 \][/tex]
4. Solve for [tex]\(x\)[/tex]:
Divide both sides by 16:
[tex]\[ x = \frac{64}{16} = 4 \][/tex]
Thus, the solution to the equation is:
[tex]\[ x = 4 \][/tex]
1. Distribute and simplify both sides:
[tex]\[ \frac{3}{5}(x - 4) + \frac{6}{7} = \frac{1}{7}(x + 2) \][/tex]
Distribute [tex]\(\frac{3}{5}\)[/tex] on the left side:
[tex]\[ \frac{3}{5}x - \frac{3}{5} \cdot 4 + \frac{6}{7} = \frac{3}{5}x - \frac{12}{5} + \frac{6}{7} \][/tex]
Distribute [tex]\(\frac{1}{7}\)[/tex] on the right side:
[tex]\[ \frac{1}{7}x + \frac{1}{7} \cdot 2 = \frac{1}{7}x + \frac{2}{7} \][/tex]
Now we have:
[tex]\[ \frac{3}{5}x - \frac{12}{5} + \frac{6}{7} = \frac{1}{7}x + \frac{2}{7} \][/tex]
2. Combine like terms:
To simplify, it is beneficial to get rid of the fractions by finding a common denominator. The common denominator for 5 and 7 is 35.
Multiply through by 35:
[tex]\[ 35 \left( \frac{3}{5}x - \frac{12}{5} + \frac{6}{7} \right) = 35 \left( \frac{1}{7}x + \frac{2}{7} \right) \][/tex]
Simplifying each term:
[tex]\[ 35 \cdot \frac{3}{5}x = 21x, \quad 35 \cdot \frac{12}{5} = 84, \quad 35 \cdot \frac{6}{7} = 30 \][/tex]
[tex]\[ 35 \cdot \frac{1}{7}x = 5x, \quad 35 \cdot \frac{2}{7} = 10 \][/tex]
So, the equation becomes:
[tex]\[ 21x - 84 + 30 = 5x + 10 \][/tex]
3. Combine like terms and isolate [tex]\(x\)[/tex]:
Simplify the equation:
[tex]\[ 21x - 54 = 5x + 10 \][/tex]
Subtract [tex]\(5x\)[/tex] from both sides:
[tex]\[ 16x - 54 = 10 \][/tex]
Add 54 to both sides:
[tex]\[ 16x = 64 \][/tex]
4. Solve for [tex]\(x\)[/tex]:
Divide both sides by 16:
[tex]\[ x = \frac{64}{16} = 4 \][/tex]
Thus, the solution to the equation is:
[tex]\[ x = 4 \][/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.